Effect of urbanisation on asthma, allergy and airways inflammation in a developing country setting. Issue 12 (5th July 2011) - Robinson, Colin L; Baumann, Lauren M; Romero, Karina; Combe, Juan M; Gomez, Alfonso; Gilman, Robert H; Cabrera, Lilia; Gonzalvez, Guillermo; Hansel, Nadia N; Wise, Robert A; Barnes, Kathleen C; Breysse, Patrick N; et al.
Abstract : Background: Asthma is a growing public health problem in developing countries. However, few studies have studied the role of urbanisation in this phenomenon. It was hypothesised that children living in a peri-urban setting in Peru have higher rates of asthma and allergy than rural counterparts. Methods: 1441 adolescents aged 13–15 years were enrolled from two settings: a peri-urban shanty town in Lima (n=725) and 23 rural villages in Tumbes (n=716). Participants filled in questionnaires on asthma and allergy symptoms, environmental exposures and sociodemographics, and underwent spirometry, and exhaled nitric oxide (eNO) and allergy skin testing. Indoor particulate matter (PM) concentrations were measured in 170 households. Results: Lima adolescents had higher rates of lifetime wheezing (22% vs 10%), current asthma symptoms (12% vs 3%) and physician-diagnosed asthma (13% vs 2%; all p <0.001). Current rhinitis (23% vs 12%), eczema (12% vs 0.4%), atopy (56% vs 38%), personal history of cigarette smoking (7.4% vs 1.3%) and mean indoor PM (31 vs 13 μg/m 3 ) were also higher in Lima (all p <0.001). The peri-urban environment of Lima was associated with a 2.6-fold greater odds (95% CI 1.3 to 5.3) of asthma in multivariable regression. Forced expiratory volumes were higher and FEV1 /FVC (forced expiratory volume in 1 s/forced vital capacity) ratios were lower in Lima (all p <0.001). Higher eNO values in Lima (p <0.001) were attributable to higher rates of asthma and atopy. Conclusions: Peri-urban adolescents had more asthma, atopy and airways inflammation and were exposed to more indoor pollution. The findings provide evidence of the risks posed to lung health by peri-urban environments in developing countries.